2018
DOI: 10.3846/jcem.2018.301
|View full text |Cite
|
Sign up to set email alerts
|

A real-time control approach based on intelligent video surveillance for violations by construction workers

Abstract: Abstract. The unsafe behavior of workers is the main object of construction safety management, in which violations require increased attention due to their pernicious consequences. However, existing studies have merely discussed violations separately from unsafe behaviors. To respond quickly to workers' violations on site, this study proposes a real-time control approach based on intelligent video surveillance. First, scenes reflecting unsafe behaviors are automatically acquired through camera-based behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[20]. Within workplaces, the most common safety violations are failure to effectively communicate the risks of workplace hazards, failure to provide fall protection, and failure to place sufficient protective equipment between workers and dangerous machinery [21]. Therefore, it is important for employers to enforce safety rules and regulations in order to avoid potential accidents.…”
Section: Violation Of Safety Rules and Regulationsmentioning
confidence: 99%
“…[20]. Within workplaces, the most common safety violations are failure to effectively communicate the risks of workplace hazards, failure to provide fall protection, and failure to place sufficient protective equipment between workers and dangerous machinery [21]. Therefore, it is important for employers to enforce safety rules and regulations in order to avoid potential accidents.…”
Section: Violation Of Safety Rules and Regulationsmentioning
confidence: 99%
“…Wang et al ( 89 ) proposed a prototype system for real-time positioning and tracking of coal miners based on a self-organizing sensor network with higher positioning accuracy and adaptability to understand the position of underground personnel in real time. Guo et al ( 90 ) suggested a real-time control method based on intelligent video surveillance, which can help control the violations of construction personnel through real-time monitoring and analysis, and promote the safety management of construction behavior. Qian et al ( 91 ) proposed an adaptive construction and update method based on a quantum-behaved particle swarm optimization–user-location trajectory feedback (QPSO–ULTF) for a radio fingerprint database, which has a good positioning effect and can ensure the normal operation of the personnel positioning system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khan [ 11 ] evaluated fire safety performance according to the characteristics of multi-story garment (RMG) buildings in India, and Zermane [ 12 ] used fault tree analysis to assess the risk of high-altitude work in Malaysian buildings. Chih [ 13 ] studied the negative impact of psychological contract breach (PCB) on workers’ safety, Guo [ 14 ] used an intelligent video surveillance method to carry out an early warning of workers’ illegal behaviors, and Chatzimichailidou [ 15 ] studied the safety risk of modular construction in the construction industry. Although these studies have revealed the causes of workers’ unsafe behaviors to a certain extent, they are limited to traditional buildings and rarely involve new trends such as prefabricated buildings.…”
Section: Literature Reviewmentioning
confidence: 99%